(untitled) (ADI Journal on Recent Innovation (AJRI), 2023)
This study aimed to examine the influence of cost focus and differentiation focus on business competition. The research adopted a quantitative approach, utilizing questionnaires distributed to a sample of 70 business actors who participated by completing questionnaires. The results support the hypotheses: cost focus positively and significantly affects business competition, as evidenced by a t-value of 3.009. Moreover, cost focus has a significant impact on differentiation focus (t-value: 72.926), while differentiation focus positively influences business competition (t-value: 9.825). The study also finds that cost focus has a significant effect on business competition, mediated by differentiation focus (t-value: 82.751). These findings emphasize the importance of both cost management and differentiation strategies for enhancing business competitiveness.